Empirical analysis of Chernobyl nuclear reactor core for 5 seconds before the explosion - Matsuki, Y.; Bidyuk, P.I. (Системні дослідження та інформаційні технології, 2016)
This study uses the methodology of empirical analysis for analyzing the transient mode of the nuclear reactor core, a few second before the explosion at the time of the Chernobyl accident. The parameters were selected from the published articles [1]. A scenario was assumed for this analysis, such as the reduction of the flow rate of the Main Circulation Pump, and regression models were constructed to examine this scenario. The results of the models application were examined, and conclusions were made regarding the reduction of the flow rate of the Main Circulation Pump and the reactivity during the last few seconds to the explosion. У дослідженні використоно методологію емпіричного аналізу для вивчення перехідних процесів активної зони ядерного реактора за кілька секунд до вибуху під час аварії на Чорнобильській АЕС. Параметри вибрано з опублікованих робіт [1]. Сценарієм цього аналізу передбачено зниження швидкості потоку основного циркуляційного насоса та побудовано регресивні моделі для вивчення цього сценарію. Розглянуто результати застосованої моделі і зроблено висновки про зменшення витрат головного циркуляційного насоса та реактивності протягом останніх кількох секунд до вибуху. В исследовании использована методология эмпирического анализа для изучения переходных процессов активной зоны ядерного реактора за несколько секунд до взрыва во время аварии на Чернобыльской АЭС. Параметры выбраны из опубликованных работ [1]. Сценарием этого анализа предположено снижение скорости потока основного циркуляционного насоса и построены регрессионные модели для изучения этого сценария. Рассмотрены результаты примененной модели и сделаны выводы об уменьшении расходов главного циркуляционного насоса и реактивности в течение последних нескольких секунд до взрыва.